2011
DOI: 10.5562/cca1874
|View full text |Cite
|
Sign up to set email alerts
|

The Use of 13C NMR Spectroscopy and Comprehensive Two-dimensional Gas Chromatography, GC×GC, for Identification of Compounds Involved in Diesel Fuel Oxidative Behavior

Abstract: Abstract. An approach has been proposed combining one dimensional inverse gated 13 C NMR spectroscopy and a comprehensive two dimensional gas chromatography (GC×GC) to analyze diesel fuels prior and after oxidation under the standard conditions. Classes of hydrocarbons present before and after oxidation have been identified and quantified. A decrease in aromatic iso-and n-paraffinic hydrocarbons and an increase in the total saturated hydrocarbons have been observed after oxidation. In that respect NMR spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…One of the features that can be determined from 1 H NMR spectra is the aromaticity (Har), usually expressed as the content (in percentage) of aromatic hydrogen atoms. It can be calculated as the ratio between the sum of all aromatic hydrogen integrals (IH ar ) and the total amount of hydrogen atoms (consisting of the sum of all aliphatic and aromatic hydrogen integrals, IH aliph and IH ar ), using the previously described procedure [18,27,28]:…”
Section: Evaluation Of Crude Oil Properties By Standard Testing Methodsmentioning
confidence: 99%
“…One of the features that can be determined from 1 H NMR spectra is the aromaticity (Har), usually expressed as the content (in percentage) of aromatic hydrogen atoms. It can be calculated as the ratio between the sum of all aromatic hydrogen integrals (IH ar ) and the total amount of hydrogen atoms (consisting of the sum of all aliphatic and aromatic hydrogen integrals, IH aliph and IH ar ), using the previously described procedure [18,27,28]:…”
Section: Evaluation Of Crude Oil Properties By Standard Testing Methodsmentioning
confidence: 99%
“…It has widely been used to study petroleum and asphaltene chemistry for more than 60 years. [22][23][24][25][32][33][34] Molina et al demonstrated that the asphaltene samples isolated from various crude oils at the Colorado oil field had considerably different molecular structures, despite the same geological formation. In that study, asphaltene samples were characterized by 1 H and 13 C NMR spectroscopy.…”
Section: One-dimensional Techniquesmentioning
confidence: 99%
“…The trisolvent was evaporated to obtain the adherent insolubles. The sum of the filterable and adherent insolubles is expressed as g/m 3 and must be less than 25 g/m 3 .…”
Section: Aging Proceduresmentioning
confidence: 99%
“…Oxidation degradation is one of the most significant limiting factors for diesel fuel stability which affects the amount of insoluble sediments formed during oxidation. 2,3 It is well known that the formation of sediments during oxidation is a complex process in which many compounds of stocks are involved, but the chemical nature of fuel sediments and exact mechanism of the sediment formation are still not fully explained and understood. [4][5][6] It is generally accepted that oxidation reactions follow the free-radical mechanism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation